The Islamic creed : study to correct the erroneous information contained in the Encyclopaedia of Islam, published by Brill, Leiden - 448786 Al-Qara Daghi, Ali Mohieddine; Mimoun Mokhtari (Cairo : ISESCO, 1997)
35